Motivación del personal en la Empresa “Gran Constructor” de Mata de Cacao, de la Parroquia Febres Cordero - Cadena Pincay, Karen Ninosca (2018)
Personal motivation is essential in the actions of the human being, and important in any field of relationships, especially in the labor sector, where the person must be recognized for their interactions, abilities, abilities and purposes, which is to share life In the business world, we must take into account that work has a preponderance, which occupies the greater part of life, allowing us to live in harmony and social and economic well-being. It is essential for companies to sustain positively the incentives that are granted to employees in relation to the activities they perform, contributing to the fulfillment of business objectives and the personal goals of the workers; This motivation is essential for the increase of productivity and the integration of the work teams in the different actions, creating a pleasant and proactive atmosphere.